The autoinflammatory diseases (Swiss Medical Weekly, 2012)
The monogenic autoinflammatory syndromes are conditions caused by mutations of genes coding for proteins that play a pivotal role in the regulation of the inflammatory response. Due to their genetic nature, most of these disorders have an early onset. Clinically they are characterised by recurrent flares of systemic inflammation presenting most of the time as sudden fever episodes associated with elevation of acute phase reactants and with a number of clinical manifestations such as rash, serositis, lymphadenopathy and arthritis. Symptom-free intervals are characterised by complete wellbeing, normal growth and complete normalisation of acute phase reactants. Familial Mediterranean fever (FMF), mevalonate-kinase deficiency (MKD) and tumour necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) are the three monogenic disorders subsumed under the term periodic fevers, while a systemic inflammation dominated by a characteristic urticarial rash associated with a number of other clinical manifestations is typical of familial cold autoinflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS) and chronic infantile neurological cutaneous and articular syndrome (CINCA). These diseases represent the clinical spectrum of different mutations of a gene named cold-induced autoinflammatory syndrome 1 (CIAS-1, or NLRP3) coding for a protein called cryopyrin. Hence these disorders are also known as cryopyrin-associated periodic syndromes (CAPS). Other conditions are characterised by typical granulomatous formations (granulomatous disorders). Blau’s syndrome (familial juvenile systemic granulomatosis) presents with non-caseating granulomatous inflammation affecting the joint, skin, and uveal tract (the triad of arthritis, dermatitis and uveitis) and is associated with mutations of the NACHT domain of the gene CARD15 (or NOD2).